Sarapan, Asupan Zat Gizi Makro Dan Cairan, Persepsi Kenyamanan Suhu Ruang Terhadap Persepsi Kinerja Pekerja - Wulandari, Selly Apliyanti; Jus'at, Idrus; Mulyani, Erry Yudhya; Sa'pang, Martien; Wahyuni, Yulia (Preventia: The Indonesian Journal of Public Health, 2021)
A companies certainly want to have a good quality of human resources, so as to produce a good performance, but sometimes many companies not paying attention to the workers health especially about nutrition. Because nutrition is also one important aspect in improving the performance andproductivity. The objective of this study is to find out the relationship between breakfast, macronutrient intake, fluid intake, and perception room temperature comfort on the perception performance of workers at PT. Intan Pertiwi Industri. This research with a cross sectional research design in which the independent and dependent variables are observed and measured at the same time. The sample was 59 respondents. Data was collected using questionnaires and food record 2x24 hours. The bivariate analysis used the Pearson correlation test. Result: There is a significant relationship between energy of breakfast, protein intake, fat intake, with perception of room temperature comfort with the perception of performance P-value ≤0.05. There is an almost significant (borderline) relationship between carbohydrate intake, fluid intake with perception of performance of P-value ≤ 0.1. There is a relationship between energy of breakfast, protein intake, fat intake, perceptions of room temperature comfort with perceptions of performance. There is almost a relationship between carbohydrate intake, fluid intake and perceptions of performance.